Application Of The Simple Moving Average Method for Farming Fish Price Forecasting Systems - Mubaarok, Ahmad Husni; Bianto, Mufti Ari; Saputra, Bagus Dwi (Universitas Muhammadiyah Lamongan, 2024)
Price is one of the important things that needs to be considered as a determining factor for profit or loss on product sales as a result of price fluctuations which are very difficult to control. Price fluctuations are caused by many factors including weather, stock availability, demand and others. One of the steps to overcome the problem of price fluctuations is to forecast the entry price of fish. Forecasting is the art or science of predicting future events using past data. The purpose of this study is to apply the simple moving average method to estimate the price of farmed fish. The simple moving average method uses a number of actual demand data to generate forecast values for future requests. This method has two special properties, namely to make forecasts that require historical data over a certain period of time, the longer the moving average, the smoother the moving average will be. This study uses data on fish prices (milkfish and tilapia) daily for January 2023. The results show that the Simple moving average produces a very accurate forecast with a MAPE percentage for milkfish of 2% and tilapia of 1.97%. Keywords – Forecasting; Price; Simple Moving Average.